Waiting time during admission procedures increases social inequalities in higher education - Mélusine Boon-Falleur; Elise Huillery; Coralie Chevallier (Proceedings of the National Academy of Sciences, 2025)
Many domains in life require people to wait to access better outcomes, such as waiting in line to access prized tickets for a show, waiting to obtain a job offer from a selective firm, or being waitlisted for a prestigious university. Although waiting might be perceived as a fair mechanism to allocate resources, it may have unintended consequences on social inequalities as individuals from lower socioeconomic backgrounds (SES) may be less likely to wait. In this study, we investigate socioeconomic differences in waiting behavior during the higher education admission process in France. To do so, we leveraged a unique national database that recorded the admission behavior of every high schooler in France over a period of three years. During the admissions process, students faced a trade-off: They could either accept an immediate offer from a university or wait in the hope of receiving a preferred offer later. Results collected among 274,316 students reveal that low-SES students were significantly less likely to wait for preferred offers, even when controlling for objective costs and benefits of waiting. This led low-SES students to ultimately enroll in programs they liked less and that were less prestigious. These results highlight how admission procedures generating uncertainty and requiring students to wait may inadvertently exacerbate educational inequalities. Such systems, while efficient, can end up favoring students who wait more. This research contributes to current discussions on admission procedure fairness by illustrating that seemingly neutral algorithms can in fact deepen social inequalities if their design rewards patience.